A novel carbon nanotubes doped natural rubber nanocomposite with balanced dynamic shear properties and energy dissipation for wave energy applications - Ali Esmaeili (Results in Materials, 2023)
Mechanical characterizations of natural rubber filled with carbon-based nanomaterials were extensively studied in tensile and tear modes whereas fewer attempts have been conducted on adynamic shear condition using a double-bonded shear test piece. This is of importance since naturalrubbers are widely used as flexible membranes for wave energy harvesting devices. Therefore, thisstudy was aimed to explore the microstructural, rheological, and dynamic viscoelastic characteristics of natural rubbers filled with different Multi-Walled Carbon Nanotubes (MWCNTs) contents. A combined compounding approach was employed to ensure a homogenous CNT dispersion was achieved. Transmission electron microscopy (TEM) was performed for the materials characterization while the processability and curing parameters of the compounds were investigated using the Mooney viscosity and rheometry test. Dynamic shear properties were compared using a cyclic test performed on a double-bonded shear test piece. TEM images showed that an optimum CNTs dispersion was reached at 3 phr MWCNTs loading whereas increasing CNT content resulted in further inhomogeneity in the sample. The addition of CNTs into the natural rubber not only improved the curing properties of the compound, i.e., low scorch and curing times, but it also increased the Mooney viscosity, the rheological properties, and the dynamic shear properties of the nanocomposite compared to the pristine rubber. The Payne and Mullins effects were also observed for all compounds manifesting dependency on the CNTs content and applied strain amplitude. Finally, MWCNT enhanced the dissipated energy of the nanocomposites with respect to the neat rubber in which an increase of 1040 % in energy dissipation for 10 phr MWCNTs compared to the control at a strain amplitude of 200% was achieved.